2014
DOI: 10.3168/jds.2013-7140
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Comparison of virulence factors in Klebsiella pneumoniae strains associated with multiple or single cases of mastitis

Abstract: Klebsiella pneumoniae mastitis in dairy cattle is generally due to an opportunistic infection from the environment, resulting in large heterogeneity among mastitis-causing strains within a herd. However, in mastitis outbreaks in 4 herds, several strains of K. pneumoniae were identified as the cause of infection in multiple cows, suggesting increased ability to either cause disease or evade host defenses. In this study, differences in capsule formation and immune evasion were compared in 5 pairs of K. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The K. pneumoniae ST442/ wzi- 154 strain in this study was isolated from a case of bovine mastitis at a dairy farm in New York State in 2006 (36), which is geographically close to the location of the first reports of ST258 in New York in 2000 (37). The ST42/ wzi- 29 was isolated in 1996 from a blood stream infection in a hospital in Singapore (38).…”
Section: Discussionmentioning
confidence: 83%
“…The K. pneumoniae ST442/ wzi- 154 strain in this study was isolated from a case of bovine mastitis at a dairy farm in New York State in 2006 (36), which is geographically close to the location of the first reports of ST258 in New York in 2000 (37). The ST42/ wzi- 29 was isolated in 1996 from a blood stream infection in a hospital in Singapore (38).…”
Section: Discussionmentioning
confidence: 83%
“…Two of these studies found significant numbers of samples that were culture negative/PCR positive for Staphylococcus spp. and C. bovis Zadoks et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Clinical milk samples have been used to compare conventional culture methods to PathoProof PCR in previous studies (Cederlöf et al, 2012;Zadoks et al, 2014). With the exception of Hiitiö et al,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations